2016
DOI: 10.7324/japs.2016.60516
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of dissolution rate and intestinal stability of candesartan cilexitil

Abstract: The objective of this work was to improve the dissolution rate of candesartan cilexitil, a poorly water soluble prodrug and to reduce its premature degradation in the intestinal lumen. Binary and ternary solid dispersions (SD) of the drug with Pluronic F68, Polyvinyl pyrrolidone (PVP), Hydroxypropyl Methylcellulose (HPMC) and Tween 80 were prepared using the solvent evaporation method. The dissolution rate of the drug was monitored and the prepared SD systems were characterized using thermal analysis and Fouri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…[3,4] Candesartan is an angiotensin-receptor blocker (ARB) that may be used alone or with other agents to treat hypertension. [5] It is administered orally as the prodrug, CC, which is rapidly converted to its active metabolite, candesartan, during absorption in the gastrointestinal tract. [6] Candesartan lowers blood pressure by antagonizing the renin-angiotensin-aldosterone system (RAAS); it competes with angiotensin II for binding to the type-1 angiotensin II receptor (AT1) subtype and prevents the blood pressure increasing effects of angiotensin II.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Candesartan is an angiotensin-receptor blocker (ARB) that may be used alone or with other agents to treat hypertension. [5] It is administered orally as the prodrug, CC, which is rapidly converted to its active metabolite, candesartan, during absorption in the gastrointestinal tract. [6] Candesartan lowers blood pressure by antagonizing the renin-angiotensin-aldosterone system (RAAS); it competes with angiotensin II for binding to the type-1 angiotensin II receptor (AT1) subtype and prevents the blood pressure increasing effects of angiotensin II.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the verified potency and selectivity of CC for angiotensin-II receptors, contradiction about its effectiveness as an antihypertensive drug to attain the targeted blood pressure has been developed (10,11). Some literatures justified the low and irregular bioavailability of CC (15 to 40%) by its high lipophilicity and low aqueous solubility (12,13), while others justified it by the early degradation of the prodrug CC by the esterase enzymes existing in the intestinal lumen before its absorption yielding the parent compound C which is poorly permeable (14). It was reported that the rate of bioconversion of ester prodrugs to the active moiety is unpredictable and erratic based on the availability of the esterase enzymes in the body and the differences in the substrate specificity resulting in pharmacological and toxicological variations (15).…”
Section: Introductionmentioning
confidence: 99%
“…Q uality control (QC) tests are classified according to United States Pharmacopeia (USP) and British Pharmacopeia (BP) as official or compendial tests and non-official or non-compendial tests (1,2). Dissolution testing is an official test and a significant component of the drug development process (3,4).…”
Section: Introductionmentioning
confidence: 99%